PIV investigations on particle velocity distribution in uniform swirling regime of fluidization - Naz, M.Y. (Springer New York LLC, 2017)
In this study, hydrodynamics of spherical particles in uniform swirling regime of a fluidized bed were investigated using MATLAB supported particle imaging velocimetry (PIV). A least investigated mesh-type distributor was used to fluidize the bed particles, at different air entry angles, for future applications in coating and granulation industry. A quarter of the bed was photographed using high speed imaging technique and the respective velocity fields of the swirling particles were produced using PIV technique. The Gaussian distribution of the particle velocity profiles was predicted at low superficial air velocity; particles near the border of the bed showed relatively low velocity than that swirled in the middle of the test section. However, at high superficial velocity, the particles near the central cone moved with velocity comparable to the particle velocity in the middle of the test section. Contrarily, the particles in the vicinity of the outer bed-wall maintained their steady state motion at all superficial air velocities. The average particle velocity experienced monotonic increase for more angular air intake. The magnitude of the particle velocity reduced by 6.35 for each 3 ∘ increment in the air entry angle. © 2017, Springer-Verlag Berlin Heidelberg.